Acoustic characterization of courtrooms by a multi-criteria method - Antonio P. O. Carvalho (2008)
This paper proposes a new multi-criteria analysis model to acoustically characterize a specific type of building: the courtrooms. A Courtroom is acoustically studied regarding several criteria: their speech intelligibility (within), speech privacy (to/from contiguous rooms) and intruding noise. These characteristics are evaluated by numerical parameters that describe the sound field within and the sound insulation given by their separating walls with bordering rooms or entrance hall, and the facade. In this paper several significant acoustic parameters are used and logically weighted to find a representative unique index of evaluation of the room, the GIAE (Global Index of Acoustic Evaluation) rated on a scale for 0 (worst) to 20 (best). The acoustic parameters used are: Reverberation Time (RT) (average of 500 and 1000 Hz frequency bands), weighted normalized airborne sound level difference of walls and partitions (Dn,w according to ISO 140-4 and 717-1) and facades (D2m,n,w according to ISO 140-5 and 717-1), Rapid Speech Transmission Index (RASTI) (with sound source in the judge position and in the defendant position). The multi-criteria mathematical model is presented and numerically tested with a large selected sample of 28 courtrooms in Portugal (Height from 2.75 to 6.85 m and Volume from 150 to 880 m3).